My life as an ice cream sandwich - Zoboi, Ibi Aanu (Puffin Books, 2020)
In the summer of 1984, twelve-year-old Ebony-Grace of Huntsville, Alabama, visits her father in Harlem, where her fascination with outer space and science fiction interfere with her finding acceptance.